Expanding the chemical scope of RNA: methyltransferases to site-specific alkynylation of RNA for click labeling - Motorin, Yuri; Burhenne, Jürgen; Teimer, Roman; Koynov, Kaloian; Willnow, Sophie; Weinhold, Elmar; Helm, Mark (Nucleic acids research, 2011)
This work identifies the combination of enzymatic transfer and click labeling as an efficient method for the site-specific tagging of RNA molecules for biophysical studies. A double-activated analog of the ubiquitous co-substrate S -adenosyl- l -methionine was employed to enzymatically transfer a five carbon chain containing a terminal alkynyl moiety onto RNA. The tRNA:methyltransferase Trm1 transferred the extended alkynyl moiety to its natural target, the N2 of guanosine 26 in tRNA Phe . LC/MS and LC/MS/MS techniques were used to detect and characterize the modified nucleoside as well as its cycloaddition product with a fluorescent azide. The latter resulted from a labeling reaction via Cu(I)-catalyzed azide-alkyne 1,3-cycloaddition click chemistry, producing site-specifically labeled RNA whose suitability for single molecule fluorescence experiments was verified in fluorescence correlation spectroscopy experiments.
First published online: 30 October 2010
Gesehen am 08.09.2022